Global innovation index 2020 who will finance innovation? - World Intellectual Property Organization ( (Geneva, Switzerland WIPO, 2020)
The Global Innovation Index 2020 provides detailed metrics about the innovation performance of 131 countries and economies around the world. Its 80 indicators explore a broad vision of innovation, including political environment, education, infrastructure and business sophistication. The 2020 edition sheds light on the state of innovation financing by investigating the evolution of financing mechanisms for entrepreneurs and other innovators, and by pointing to progress and remaining challenges – including in the context of the economic slowdown induced by the coronavirus disease (COVID-19) crisis. El Índice de innovación global 2020 proporciona métricas detalladas sobre el desempeño de la innovación de 131 países y economías de todo el mundo. Sus 80 indicadores exploran una visión amplia de la innovación, incluido el entorno político, la educación, la infraestructura y la sofisticación empresarial. La edición de 2020 arroja luz sobre el estado de la financiación de la innovación al investigar la evolución de los mecanismos de financiación para emprendedores y otros innovadores, y al señalar el progreso y los desafíos pendientes, incluso en el contexto de la desaceleración económica inducida por la enfermedad del coronavirus (COVID-19). ) crisis.
Keywords: PROPIEDAD INTELECTUAL -- INNOVACIONES MEDICAS -- INFRAESTRUCTURA VIRTUAL -- EMPRESAS Y FINANZAS -- ECONOMIA MUNDIAL; LA INDIA -- FINANZAS E INNOVACION -- INDUSTRIA; BRASIL -- FINANZAS E INNOVACION -- INDUSTRIA